Measurement and modelling of the vapor–liquid equilibrium of (CO2 + CO) at temperatures between (218.15 and 302.93) K at pressures up to 15 MPa. (November 2018) - Souza, Lorena F.S.; Al Ghafri, Saif Z.S.; Trusler, J.P. Martin
Graphical abstract: Highlights: Vapour-liquid equilibrium measurements of the (CO2  + CO) system along seven isotherms. Results are compared with literature data. Performance of two thermodynamic models: the PR-EOS and the EOS-CG are assessed. EOS-CG shows significantly better agreement with the experimental data than PR-EOS, especially close to the critical point. Abstract: Precise knowledge of vapor–liquid equilibrium (VLE) data of (CO2  + diluent) mixtures is crucial in the design and operation of carbon capture, transportation and storage processes. VLE measurements of the (CO2  + CO) system are reported along seven isotherms at temperatures ranging from just above the triple-point temperature of CO2 to 302.93 K and at pressures from the vapor pressure of pure CO2 to approximately 15 MPa, including near-critical mixture states for all isotherms. The measurements are associated with estimated standard uncertainties of 0.006 K for temperature, 0.009 MPa for pressure and 0.011 x (1 −  x ) for mole fraction x . The new VLE data have been compared with two thermodynamic models: the Peng-Robinson equation of state (PR-EOS) and a multi-fluid Helmholtz-energy equation of state known as EOS-CG. The PR-EOS was used with a single temperature-dependent binary interaction parameter, which was fitted to the experimental data. In contrast, EOS-CG was used in a purely-predictive mode with no parameters fitted to the present results. While PR-EOS generally agrees fairly well with the experimental data, EOS-CG showed significantly better agreement, especially close to the critical point.